2021
DOI: 10.1093/rpd/ncab020
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality and Potential Dose Reduction Using Advanced Modeled Iterative Reconstruction (Admire) in Abdominal Ct - A Review

Abstract: Traditional filtered back projection (FBP) reconstruction methods have served the computed tomography (CT) community well for over 40 years. With the increased use of CT during the last decades, efforts to minimise patient exposure, while maintaining sufficient or improved image quality, have led to the development of model-based iterative reconstruction (MBIR) algorithms from several vendors. The usefulness of the advanced modeled iterative reconstruction (ADMIRE) (Siemens Healthineers) MBIR in abdominal CT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, this level has shown benefits in abdominal imaging. 27,28 Finally, we did not compare PCD-CT with other CT scanners of different vendors.…”
Section: Discussionmentioning
confidence: 99%
“…However, this level has shown benefits in abdominal imaging. 27,28 Finally, we did not compare PCD-CT with other CT scanners of different vendors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the MBIR algorithms can substantially improve CTP image quality compared with the filtered back-projection (FBP) (Kataria et al 2021). Meanwhile, there are some disadvantages in them.…”
Section: Mbir Methodsmentioning
confidence: 99%
“…The increasing awareness of risks associated with radiation exposure triggered a variety of dose-reduction techniques, such as tube current or tube voltage modulation, automatic exposure control, and low-kilovolt scanning [26], where a dose reduction between 10% and 30% is possible, depending on examination type. Compared to the real-time analytical reconstruction method, filtered back projection (FBP) [27], which has reached its limitation and does not allow for further dose reductions, vendor-specific iterative reconstruction algorithms were introduced, which allow further dose reductions [28,29].…”
Section: Gan Manufacture and Ganificationmentioning
confidence: 99%